2006
DOI: 10.1007/s00203-006-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the putative tetracycline resistance gene HP1165 in Helicobacter pylori led to loss of inducible tetracycline resistance

Abstract: Tetracycline has been used with other antibiotics in treatment of Helicobacter pylori infection. However, tetracycline resistance has developed in H. pylori clinical isolates, rendering treatment failure. Mutations in 16S rRNA genes have been reported to mediate tetracycline resistance in some isolates. The diversity of tetracycline resistance cases suggests multiple genes are involved. HP1165, a putative tetracycline resistance gene in H. pylori 26695, displays 49.8% identity to the tetracycline efflux gene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Indeed, Dailidiene et al suggested that tetracycline resistance could result from an accumulation of changes that may affect tetracycline-ribosome affinity and/or other functions such as porins or efflux pumps (92). In 2006, a putative tetracycline resistance gene, HP1165, which displays identity to the tetracycline efflux gene tetA from Clostridium perfringens was found to be involved in some strains in the inducible tetracycline resistance in H. pylori (309). Several nonspecific multidrug resistance proteins have also been described, but their importance needs to be clarified (279,396,479,541).…”
Section: Resistance Mechanismsmentioning
confidence: 99%
“…Indeed, Dailidiene et al suggested that tetracycline resistance could result from an accumulation of changes that may affect tetracycline-ribosome affinity and/or other functions such as porins or efflux pumps (92). In 2006, a putative tetracycline resistance gene, HP1165, which displays identity to the tetracycline efflux gene tetA from Clostridium perfringens was found to be involved in some strains in the inducible tetracycline resistance in H. pylori (309). Several nonspecific multidrug resistance proteins have also been described, but their importance needs to be clarified (279,396,479,541).…”
Section: Resistance Mechanismsmentioning
confidence: 99%
“…The triple-base pair 16S rDNA mutations, namely AGA (926-928) ? A high level of evolutionary pressure on H. pylori to acquire TET resistance is also evident from the identification of other mechanisms, like those involving the hp1165 gene, a putative TET resistance gene in H. pylori 26695 [91], which may be associated with the inducible TET resistance in H. pylori. Novel TET resistanceconferring mutations, such as A939C and site substitution (965-967), have yet to be identified [89,90].…”
Section: Resistance To Tetmentioning
confidence: 99%
“…Novel TET resistanceconferring mutations, such as A939C and site substitution (965-967), have yet to be identified [89,90]. A high level of evolutionary pressure on H. pylori to acquire TET resistance is also evident from the identification of other mechanisms, like those involving the hp1165 gene, a putative TET resistance gene in H. pylori 26695 [91], which may be associated with the inducible TET resistance in H. pylori.…”
Section: Resistance To Tetmentioning
confidence: 99%
“…In many Gram-negative bacteria, resistance to tetracycline is also related to an energy-dependent efflux of Tet across the cell membrane (Chopra & Roberts, 2001;Nikaido, 1998). Although several investigators have studied the probable role of active efflux in the intrinsic resistance of H. pylori to antibiotics (Bina et al, 2000;Kutschke & de Jonge, 2005;Li & Dannelly, 2006;van Amsterdam et al, 2005), there are no data concerning the precise role of this mechanism in resistance to Tet. In a recent study, Wu et al (2005) examined whether Tet resistance was associated with an energy-coupled active efflux mechanism.…”
Section: Introductionmentioning
confidence: 99%